Single-carbon discrimination by selected peptides for individual detection of volatile organic compounds - Ju, Soomi; Lee, Ki-Young; Min, Sun-Joon; Yoo, Yong Kyoung; Hwang, Kyo Seon; Kim, Sang Kyung; Yi, Hyunjung (NATURE PUBLISHING GROUP, 2015)
Although volatile organic compounds (VOCs) are becoming increasingly recognized as harmful agents and potential biomarkers, selective detection of the organic targets remains a tremendous challenge. Among the materials being investigated for target recognition, peptides are attractive candidates because of their chemical robustness, divergence, and their homology to natural olfactory receptors. Using a combinatorial peptide library and either a graphitic surface or phenyl-terminated self-assembled monolayer as relevant target surfaces, we successfully selected three interesting peptides that differentiate a single carbon deviation among benzene and its analogues. The heterogeneity of the designed target surfaces provided peptides with varying affinity toward targeted molecules and generated a set of selective peptides that complemented each other. Microcantilever sensors conjugated with each peptide quantitated benzene, toluene and xylene to sub-ppm levels in real time. The selection of specific receptors for a group of volatile molecules will provide a strong foundation for general approach to individually monitoring VOCs.
Keywords: PULMONARY-DISEASES; SENSOR; BIOMARKERS; BENZENE; MICROCANTILEVER; NANOSTRUCTURES; EXPLOSIVES; LEUKEMIA; BINDING